CO2 captured in zeolitic imidazolate frameworks: Raman spectroscopic analysis of uptake and host-guest interactions - A. G. Kontos; V. Likodimos; Veziri, C.M.; Kouvelos, E.; Moustakas, N.; Karanikolos, G.N.; Romanos, G.E.; P. Falaras (ChemSusChem, 2014)
Zeolitic imidazolate frameworks (ZIFs) exhibit enhanced selectivity and increased CO2 uptake due to the incorporation of functional imidazolate units in their structure as well as their extensive porosity and ring flexibility. In situ Raman investigation of a representative host compound, ZIF-69, in practical CO2 pressure and temperature regimes (0-10 bar and 0-64 °C) correlates well with corresponding macroscopic CO2 sorption data and shows clear clear spectroscopic evidence of CO2 uptake. Significant positive shift of the 159 cm-1 phenyl bending mode of the benzimidazole moiety indicates weak hydrogen bonding with CO 2 in the larger cavities of the ZIF matrix. Raman spectroscopy is shown to be an easy and sensitive tool for quantifying CO2 uptake, identifying weak host-guest interactions and elucidating CO2 sorption mechanism in ZIFs. Are you Raman enough? In situ Raman investigation of the interactions of zeolitic imidazolate frameworks (ZIFs) with CO2 in practical pressure and temperature regimes (0-10 bar and 0-64 °C) correlates well with corresponding macroscopic CO2 sorption data and shows clear spectroscopic evidence of CO2 uptake (see image). Raman is found to be an easy and sensitive tool for quantifying CO2 uptake, identifying weak host-guest interactions, and elucidating CO2 sorption mechanism in ZIFs. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.